Combating Cybercrime and Cyberterrorism in Indonesia - Cynthia Shafira Hartati; Ali Muhammad (Jurnal Hubungan Internasional, 2023)
Cybercrime poses a serious risk to national security in Indonesia. The pervasive nature of cybercrime calls into question the efficacy of current regulatory measures. The study objective reflects how the government addresses sustaining securitization in cyberspace. This study employed a descriptive qualitative method to analyze the impact of cybercrime in Indonesia and the regulations with an extremely high intercorrelation. Terrorism, both on the ground and digitally, has been on the rise at an alarming rate in recent years. The influence of universal access to all relevant information has several implications, including the propagation of misinformation and the growth of cybercrime networks. There must be significant disruption to the cyberterrorism industry to foster safe circumstances in Indonesia. The success of Indonesia’s regulatory efforts depends on the contribution and synergy between the government and the public.